Unraveling the biology of auditory learning: A cognitive-sensorimotor-reward framework - Kraus, Nina (Trends Cogn Sci, 2015)
The auditory system is stunning in its capacity for change: a single neuron can modulate its tuning in minutes. Here we articulate a conceptual framework to understand the biology of auditory learning, where an animal must engage cognitive, sensorimotor, and reward systems to spark neural remodeling. Central to our framework is a consideration of the auditory system as an integrated whole that interacts with other circuits to guide and refine life in sound. Despite our emphasis on the auditory system, these principles may apply across the nervous system. Understanding neuroplastic changes in both normal and impaired sensory systems guides strategies to improve everyday communication.